2009
DOI: 10.1017/s0043933909000312
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of flock productivity through supply of vitamins for higher laying performance and better egg quality

Abstract: An adequate supply of all nutrients, including proteins, fats, carbohydrates, vitamins, minerals and water, has to be provided to support maximum productivity of laying hens. Among these nutrients, vitamins are particularly important, since they are essential for optimum health as well as normal physiological functions of the hens. As most vitamins cannot be synthesized by poultry in sufficient amounts to meet physiological demand, they must be obtained from the diet. The absence from feed or impaired absorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 41 publications
0
26
0
Order By: Relevance
“…Vitamin E, selenium and carotenoids are the prime antioxidant components in poultry feed (Surai & Kochish, 2019). Weber (2009) reported that deficiency signs of clinical vitamin E include exudative diathesis, muscular myopathy and encephalomalacia in chicks (disturbance of the nervous system), as well as some subclinical vitamin E deficiency such as slow growth performance, diminished fertility and frequent health problems. Therefore, the antioxidant properties of vitamin E were investigated regarding its vital role in the prevention of diseases that occur due to lipid peroxidation and protein oxidation via a free radical mechanism (Colombo 2010; Rizvi et al 2014).…”
Section: Vitamin Ementioning
confidence: 99%
See 2 more Smart Citations
“…Vitamin E, selenium and carotenoids are the prime antioxidant components in poultry feed (Surai & Kochish, 2019). Weber (2009) reported that deficiency signs of clinical vitamin E include exudative diathesis, muscular myopathy and encephalomalacia in chicks (disturbance of the nervous system), as well as some subclinical vitamin E deficiency such as slow growth performance, diminished fertility and frequent health problems. Therefore, the antioxidant properties of vitamin E were investigated regarding its vital role in the prevention of diseases that occur due to lipid peroxidation and protein oxidation via a free radical mechanism (Colombo 2010; Rizvi et al 2014).…”
Section: Vitamin Ementioning
confidence: 99%
“…Moreover, vitamin E has a significant role in the improvement of health by boosting both humoral and cell-mediated immune functions (Rizvi et al 2014). Vitamin E protects the phospholipids of sub-cellular and cellular membranes from the destruction by the lipid oxidation and therefore maintains the functionality and morphological integrity of tissues and cells of the organism (Weber 2009). Vitamin E has been found to improve antioxidant defense, immune response and physiological functions of birds (Habibian et al 2014;Min et al 2018).…”
Section: Vitamin Ementioning
confidence: 99%
See 1 more Smart Citation
“…Biotin is a coenzyme that has fundamental roles in carbohydrate, protein, and lipid metabolism [ 116 ]. Diets containing inadequate amounts of biotin can lead to fatty liver and kidney syndrome, a low hatchability rate, low growth rate, and the increased occurrence of foot pad dermatitis in birds [ 114 119 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thiamine or vitamin B 1 acts as a co-enzyme that participates in the oxidative decarboxylation of pyruvic acid and α-ketoglutaric acid, thereby leading to the production acetyl-coenzyme A (CoA) and succinyl-CoA, which are involved in the metabolism of carbohydrates, proteins, and lipids [ 116 ]. Feeding poultry a diet deficient in thiamine leads to reductions in appetite, growth, carcass yield, and hatchability, as well impaired carbohydrate metabolism and a high mortality rate [ 147 150 ].…”
Section: Introductionmentioning
confidence: 99%